COMPARISON OF SPECIFIC GROWTH OF VARIOUS TYPES OF CAULERPA CULTIVATED IN TRAY ON BARRANG CADDI ISLAND, MAKASSAR CITY - Rahmadani Rahmadani; Muh. Imran Lapong (Journal of Fisheries and Marine Resource Management, 2026)
This study compared the growth performance of three Caulerpa species cultivated in tray systems on sandy substrates at Barrang Caddi Island, Makassar City, Indonesia. The experiment was conducted for 14 days using Caulerpa lentillifera, Caulerpa racemosa, and Caulerpa cylindracea under similar environmental conditions. Growth performance was evaluated based on absolute biomass growth, specific growth rate (SGR), and frond length, while water quality parameters, including temperature, salinity, and pH, were monitored to assess environmental suitability. Data were analyzed descriptively and statistically using Tukey's multiple comparison test. The results showed that all three species exhibited growth throughout the cultivation period. Caulerpa racemosa produced the highest biomass gain and specific growth rate, indicating greater adaptability to sandy substrates and more efficient nutrient utilization than the other species. In contrast, Caulerpa lentillifera achieved the greatest frond elongation, suggesting its suitability for fresh edible sea grape production. Water quality remained within the optimal range for tropical Caulerpa cultivation, with average values of 27.7°C for temperature, 29.7 PSU for salinity, and pH 8.33. These favorable environmental conditions supported continuous growth and physiological performance throughout the experiment. Overall, tray cultivation on sandy substrates proved to be a feasible cultivation method for Caulerpa, with C. racemosa recommended for maximizing biomass production and C. lentillifera preferred for commercial production targeting high-quality edible fronds. These findings provide valuable information for improving sustainable sea grape aquaculture in tropical coastal ecosystems.